STATUS BEBERAPA SIFAT KIMIA TANAH PADA BERBAGAI PENGGUNAAN LAHAN DI DAS POBOYA KECAMATAN PALU SELATAN - Abdul Rahim Thaha,Isrun, Ilham Bakri (AGROTEKBIS, 2016)
This research aim was to determine various soil chemical properties on a variety land uses in Poboya watershed. A survey method was employed through which soil samples were tactically taken.  The distance between one soil sample to another was determined according to the condition of the research area.  Four different types of land uses i.e. forest, bushes, mixed plantation and dryland cultivation were surveyed.  Five sub soil samples were compositely obtained from each land use, thus, there were four composite soil samples were for laboratory analysis.  The analysis included soil pH, organic C, total N, total P, available P, K, cation exchangeable capacity and texture.  The results of the analysis showed that the forest land has better soil chemical characteristics than the other land uses.  The chemical characteristics of the mixed plantation and dryland cultivation are generally were relatively low.